MAQASHID, MUSLIM DEVOTION AND RAMADHAN TRADITION IN PANDEMIC TIMES - Nur Lailatul Musyafaah (State of Islamic Institute Langsa, 2021)
This article discusses the implementation of Ramadan worship during the Covid-19 pandemic which is then analyzed by maqashid shari’ah. Due to the Covid-19 pandemic, the government issued a policy of encouraging worship at home only so that it could minimize the transmission of covid-19. From the results of the study, it is known that there are still mosques that open for Ramadan worship, and there are still many respondents who perform worship at the mosque (obligatory prayers, tarawih, tadarrus, and Eid prayers). In the perspective of maqashid shari’ah, if the respondent chooses to worship outside the home by complying with the regulations according to health protocols, this is by the principles of hifz al-din and hifz al-nafs. But if they do not heed it, then it is against hifz al-din and hifz al-nafs in maqashid shari’ah.